Nasolabial flap in oral sub mucous fibrosis - Our experience and review - Ahtesham Ahmad; Syed Ahmed; Nawab P. Jamadar; Sheeraz Badal; Arshiya A. Jamadar; Nilofar Ahtesham (Al Ameen Medical College, 2016)
Background & Objectives: Oral submucous fibrosis (OSMF) is a pre-melignant condition which results in progressive closure of the mouth. Management is predominantly in the realm of surgery. The procedure consists of releasing of all the buccal fibrotic bands followed by reconstruction of the defect. From among the various reconstructive modalities available, the nasolabial flap is the most versatile attributed to its reliable vascularity and offers itself as an attractive option for reconstruction of regional intraoral defects. In our study, we evaluate the effectiveness of the nasolabial flap in the reconstruction of the defect created after releasing of the fibrotic bands in patients with oral submucous fibrosis. Methods: 12 cases of oral submucous fibrosis who reported to the Department of Oral and Maxillofacial Surgery, MIDSR, Dental College and Hospital, latur were selected in this study and treated with surgical releasing of fibrotic bands and reconstruction of the resultant defect with nasolabial flap. Results: No case of wound dehiscence or necrosis, obstruction of Stenson's duct, damage to facial artery and facial nerve branches were observed post operatively. The postoperative mouth opening was 20-40 mm (Mean: 36.416 mm) after 6 months follow up and the mean increase was 24.916 mm. The only notable complication was intraoral hair growth in some patients. Interpretation & Conclusion: The results of our study have led us to the conclusion that the nasolabial flap offers itself as an effective and predictable modality of reconstruction in cases of OSMF.